The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2005
DOI: 10.1038/sj.bjc.6602586
|View full text |Cite
|
Sign up to set email alerts
|

Phase I trial combining gemcitabine and treosulfan in advanced cutaneous and uveal melanoma patients

Abstract: Gemcitabine and treosulfan are DNA-damaging agents. Preclinical studies suggest that synergism exists when melanoma cells are exposed to both drugs concurrently. We conducted a phase I trial in advanced melanoma patients to determine the optimal dose of gemcitabine to be combined with treosulfan. Cohorts of three patients received increasing doses of gemcitabine, commencing at 0.5 g m À2 , followed by a fixed dose of 5.0 g m À2 treosulfan on day one of a 21-day cycle. Patients alternately received a first cycl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 21 publications
0
17
0
Order By: Relevance
“…This can be used to measure crosslinking in lymphocytes or solid tumour material where samples are taken following treatment of patients with drugs such as ifosfamide , treosulfan (Corrie et al, 2005) or antibody directed enzyme pro-drug therapy (Webley et al, 2001). Alternatively, it can be used to measure crosslink formation and repair in cells isolated from patients and treated ex vivo with drug as in the present study, or as previously demonstrated in myeloma plasma cells treated with melphalan (Spanswick et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This can be used to measure crosslinking in lymphocytes or solid tumour material where samples are taken following treatment of patients with drugs such as ifosfamide , treosulfan (Corrie et al, 2005) or antibody directed enzyme pro-drug therapy (Webley et al, 2001). Alternatively, it can be used to measure crosslink formation and repair in cells isolated from patients and treated ex vivo with drug as in the present study, or as previously demonstrated in myeloma plasma cells treated with melphalan (Spanswick et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…We have previously demonstrated that a modification of the single cell gel electrophoresis (comet) assay can be used successfully in the clinical setting to detect and quantify the levels of ICLs in patient lymphocytes and tumour cells at pharmacologically relevant doses of bifunctional alkylating agents Webley et al, 2001;Spanswick et al, 2002;Corrie et al, 2005). The method has also been used to measure cisplatin-induced ICLs in vitro (De Silva et al, 2002).…”
mentioning
confidence: 99%
“…It is now increasingly used to monitor ICL formation and unhooking in clinical samples (30,40) as a pharmacodynamic end point in clinical trials (41,42), and following ex vivo treatment (39,43).…”
Section: Discussionmentioning
confidence: 99%
“…A phase I trial in this disease suggested a synergistic effect between the two agents, with gemcitabine causing the persistence of treosulfaninduced DnA interstrand crosslinks (4).…”
Section: Introductionmentioning
confidence: 99%